Increased Density of Prohibitin-Immunoreactive Oligodendrocytes in the Dorsolateral Prefrontal White Matter of Subjects with Schizophrenia Suggests Extraneuronal Roles for the Protein in the Disease - Bernstein, Hans-Gert; Smalla, Karl-Heinz; Dürrschmidt, Diana; Keilhoff, Gerburg; Dobrowolny, Henrik; Steiner, Johann; Schmitt, Andrea; Kreutz, Michael R.; Bogerts, Bernhard (Neuromolecular medicine, 2012)
Prohibitin has previously been implicated in the synaptic pathology of schizophrenia. The recently discovered abundant expression of prohibitin in human prefrontal oligodendrocytes raises the issue, whether this protein might also be part of the well-known white matter abnormalities in schizophrenia. Hence, post-mortem brains of ten patients with schizophrenia and ten matched control cases were investigated. Using a direct, 3D-counting technique we morphometrically analyzed the number and density of prohibitin-immunoreactive oligodendroglial cells in the left and right dorsolateral, anterior cingulate, and orbitofrontal cortex white matter. Additionally, we studied the prohibitin expression in different neuronal and non-neuronal cell populations in rat cell cultures. We could confirm the strong expression of prohibitin in oligodendrocytes. Intracellularly, the protein was localized to mitochondria and some cell nuclei. In schizophrenia, the numerical density of prohibitin-expressing oligodendrocytes was significantly increased in the right dorsolateral white matter area. Taking into consideration the dual intracellular localization of prohibitin in oligodendrocyte mitochondria and cell nuclei, one may suggest an involvement of the protein in mitochondrial dysfunction and/or cycle abnormalities in schizophrenia.